The Moldovan leaders’ ethno-confessional policies from the XIVth–XVIIth centuries - Zabolotnaia, Lilia (Balcanica Posnaniensia. Acta et studia, 2011)
The article concerns the ethno-confessional policies of Moldovan rulers from the fourteenth to the seventeenth century. The author analyzes the multiethnic and multiconfessional character of Moldovan towns and the relations among Orthodox, Catholic, and other ethnic groups inhabiting Moldavia. The subject is important for research on the socio-religious history of Southeastern Europe and the functioning of the Moldovan state at the intersection of the Latin, Orthodox, and Ottoman worlds. The aim of the article is to demonstrate how the policies of Moldovan hospodars influenced the development of urban communities and confessional relations. The author employs historical source analysis, focusing primarily on legal documents and privileges granted to foreign merchants and craftsmen. The study demonstrates that Moldovan rulers consciously encouraged the influx of foreign ethnic groups — especially Hungarians, Saxons, Poles, and Greeks — by offering them economic and fiscal privileges. At the same time, Catholics constituted an important element of urban life, although their numbers gradually declined as a result of assimilation into the local population. The results of the analysis indicate that policies of tolerance and economic pragmatism contributed to the development of Moldovan towns and strengthened their multicultural character.